2010
DOI: 10.1007/s10577-010-9130-2
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of CMA bands in Citrus and related genera

Abstract: Most species of Citrus and related genera display a similar karyotype with 2n = 18 and a variable number of terminal heterochromatic blocks positively stained with chromomycin A(3) (CMA(+) bands). Some of these blocks are 45S rDNA sites, whereas others may correspond to the main GC-rich satellite DNA found in several Citrus species. In the present work, the distribution of the 45S rDNA and the main satellite DNA isolated from C. sinensis (CsSat) were investigated by in situ hybridization in seven species of Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 32 publications
12
42
0
Order By: Relevance
“…Blutorange and C. paradisi cv. Ruby Red were identical to those previously described for these species [Pedrosa et al, 2000;Cornélio et al, 2003;Moraes et al, 2007a;Barros e Silva et al, 2010]. The hybrid C. reticulata !…”
Section: Karyotype and Genome Size Of The Genus Citrussupporting
confidence: 71%
“…Blutorange and C. paradisi cv. Ruby Red were identical to those previously described for these species [Pedrosa et al, 2000;Cornélio et al, 2003;Moraes et al, 2007a;Barros e Silva et al, 2010]. The hybrid C. reticulata !…”
Section: Karyotype and Genome Size Of The Genus Citrussupporting
confidence: 71%
“…Furthermore, Yamamoto et al [2009] reported a single pair of 5S rDNA sites in chromosomes of Citropsis gabunensis, Citrus reshni, Fortunella japonica, Clymenia polyandra and Swinglea glutinosa and in 3 pairs in Poncirus trifoliata , but they did not investigate the position of 45S rDNA. Likewise, the number of 45S rDNA sites was previously reported for several Citrus species [Kang et al, 2008;Marques et al, 2011] and some related genera [Barros e Silva et al, 2010]. However, simultaneous detection of 5S and 45S rDNA sites in the same cell was previously reported only for P. trifoliata and Citrus species of the subgenus Citrus [Pedrosa et al, 2000;Carvalho et al, 2005;Brasileiro-Vidal et al, 2007;Moraes et al, 2007a, b].…”
mentioning
confidence: 70%
“…For example, if one of the 2 bands of a C chromosome undergoes a strong size reduction, the chromosome will look like a D type, or vice-versa [Moraes et al, 2007b]. Change from a D-type chromosome to a C or F type, for example, seems to have occurred several times in the subfamily Aurantioideae [Barros e Silva et al, 2010;Mendes et al, 2011]. In M. paniculata , a D chromosome pair was previously misinterpreted as a B pair because the occurrence of a secondary constriction in the CMA band [Guerra et al, 2000], but when observed with FISH, it became clear that the correct formula was 2C + 14D + 2F [Barros e Silva et al, 2010].…”
Section: Variation Of Cma Bands and Rdna Sites In An Apparently Stablmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the multitude of mechanisms capable of producing different patterns, variations in heterochromatin patterns have been used to confirm the taxonomic placements of numerous taxa. Citrus is a good example, as the seven chromosomes types described by Guerra (1993) and Cornélio et al (2003) have been widely used to distinguish between different specimens, cultivars, and hybrids -even species of related genera (Cornélio et al 2003, Carvalho et al 2005, Barros e Silva et al 2010.…”
Section: Discussionmentioning
confidence: 99%